(untitled) (Contemporary Mathematics, 2024)
In this article, a new inequality on Jain-Saraswat divergence measure is investigated for s-convex functions, which includes convex functions as a special case. Further, by using this inequality, some special results have also been derived in terms of the different divergences, at distinct values of s. Numerical verification of these results has also been discussed.